The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1007/s10384-005-0319-4
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Array-Generated Cytokine Profiles of Tears of Patients with Vernal Keratoconjunctivitis or Giant Papillary Conjunctivitis

Abstract: The present study demonstrated the presence of crucial cytokines, soluble cytokine receptors, and chemokines in tears of patients with VKC and GPC. In particular, IL-6sR increased significantly in both the VKC and GPC groups, whereas eotaxin-2 increased significantly only in the VKC group. Thus, IL-6sR may play an important pathophysiological role in giant papillary proliferation in VKC and GPC, and eotaxin-2 may play an important role in eosinophilic inflammation in VKC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 28 publications
(25 reference statements)
1
31
0
Order By: Relevance
“…[1][2][3]10,19,22,[26][27][28][29]31,33,34 The cell traffic (migration) can be realized not only by means of attraction mechanisms, governed by attraction and/or chemotactic factors and adhesion molecules, but also through the so-called 'homing' mechanism of the B-and T-lymphocytes, being controlled by a number of homing factors. 1,10,22,26,27,31,32,[35][36][37][38] The disturbed homing mechanisms can then lead to the migration of the particular cell types to different localities.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3]10,19,22,[26][27][28][29]31,33,34 The cell traffic (migration) can be realized not only by means of attraction mechanisms, governed by attraction and/or chemotactic factors and adhesion molecules, but also through the so-called 'homing' mechanism of the B-and T-lymphocytes, being controlled by a number of homing factors. 1,10,22,26,27,31,32,[35][36][37][38] The disturbed homing mechanisms can then lead to the migration of the particular cell types to different localities.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of chemokine profi les in tears of patients with VKC has shown that eotaxin-1 and -2 are critical chemokines in the pathogenesis of VKC. 15,23 Our current results showed that detection of both eotaxin-1 and eotaxin-2 in tears may indicate an advanced stage of VKC. The concentration of eotaxin-2 in tears is thus a suitable scale biomarker for the allergic infl ammatory intensity in VKC patients.…”
Section: Discussionmentioning
confidence: 87%
“…14 In our previous antibody-array analysis study of cytokine and chemokine profi les in tears of patients with VKC and giant papillary conjunctivitis (GPC), eotaxin-2 and soluble interleukin-6 receptor increased signifi cantly in patients with VKC or GPC compared with in healthy individuals. 15 However, the biological role of the eotaxin subfamily in the pathogenesis of VKC is not fully understood. Furthermore, a recent report has suggested that conjunctival epithelial cells are capable of actively participating in immune reactions via the production of cytokines and chemokines such as interleukin (IL)-6, IL-8, and eotaxin.…”
mentioning
confidence: 99%
“…Median values are presented with the range in parentheses. 1 Mann-Whitney U test. n-fold change = value of mRNA in AKC-iCALT/value of mRNA in AKC-conjunctiva.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the proliferative conjunctival lesions (e.g. giant papillae and limbal gelatinous infiltration), the clinical characteristics of patients with AKC or VKC include high serum levels of antigen-specific IgE antibodies, increased expression and secretion of inflammatory cytokines (IL-4, IL-5), soluble cytokine receptors (soluble IL-6 receptor), and chemokines (eotaxin, IL-8) in tears [1][2][3][4][5][6] . In particular, high levels of these cytokines and chemokines in the tears of patients with severe ACD are thought to originate from the conjunctival epithelium and lacrimal gland, and the mast cells, eosinophils and type 2 helper T (Th2) cells in conjunctival tissue, and play a critical role in the pathogenesis of allergic inflammation.…”
Section: Introductionmentioning
confidence: 99%